Perencanaan Surveilans Brucellosis pada Manusia di Jawa Barat dengan Menggunakan Metode Geographical Information System (GIS) - Novita, Risqa (Jurnal Biotek Medisiana Indonesia, 2014)
Brucellosis is a zoonotic disease transmitted from animals and humans. The main source of brucellosis are ruminant animals such as dairy cows and sheep. Symptoms of human brucellosisis acute and non-specific that the reporting of cases are very rare. GIS-based surveillance is needed to detect Brucellosis disease patterns so that it can be made effective prevention programs, it aims to achieve optimal public health.The study was a reviewer from literature in Google and Pubmed by searching keywords are human Brucellosis, surveilance of human brucellosis and geographical information system (GIS). Based on the results of the literature searching, the use of GIS methods in human Brucellosis surveillance is still rare due to the low number of recording cases of Brucellosis in humans.Publics are also not know that brucellosis is zoonotic disease, furthermore clinical symptoms of brucellosis is acute and not specific.Surveillance of Brucellosis using GIS methods is necessary to ensure the prevention of brucellosis in animals and humans can be performed effectively in order to reach animal and human health systems are optimal.Key words : Human brucellosis, Surveillance, GISÂ AbstrakBrucellosis adalah penyakit yang ditularkan dari binatang ke manusia. Sumber penularan utama brucellosis adalah sapi perah dan domba. Gejala klinis brucellosis pada manusia bersifat akut dan tidak spesifik, sehingga catatan laporan kasus brucellosis di manusia sangat jarang. Surveilans yang berbasis Geographical Information System (GIS) diperlukan untuk mendeteksi brucellosis sehingga dapat menghasilkan program pencegahan yang efektif sehingga akan tercapai kesehatan masyarakat yang optimal. Kajian ini merupakan hasil dari telaah literatur hasilpenelusuran internet yang didapatkan dari Pubmed, CDC, FAO dan WHO melalui pencarian kata kunci yaitu brucellosis manusia dan GIS. Berdasarkan dari pencarian literatur, penggunaan GIS dalam surveilans manusia masih sangat jarang karena rendahnya angka pelaporan kasus brucellosis di manusia. Masyarakat belum banyak yang mengetahui potensi zoonosis dari brucellosis ditunjang gejala klinis yang ditimbulkan bersifat akut dan tidak spesifik. Surveilans brucellosis memakai metode GIS penting untuk menetapkan program pencegahan brucellosis di hewan dan manusia yang efektif agar tercapai sistem kesehatan manusia yang optimal.Kata Kunci : Brucellosis manusia, Surveilans, GIS